2020
DOI: 10.1021/acsomega.0c02618
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pomegranate Extract-Loaded Solid Lipid Nanoparticles: Quality by Design Approach to Screen the Variables Affecting the Quality Attributes and Characterization

Abstract: The aim of this work was to study the influence of process variables on the quality attributes of pomegranate extract loaded solid lipid nanoparticles (PE-SLNs) using Plackett–Burman design. PE-SLN formulations were prepared by hot homogenization followed by ultra-sonication technique and evaluated based on the dependent variables that were analyzed utilizing Statgraphics Centurion XV software. The lipid and surfactant (type and concentration), co-surfactant concentration, sonication time, and amplitude were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 57 publications
4
30
1
Order By: Relevance
“… Akbarian et al (2016) have found that the biological availability of orally supplemented basil seeds is very tracing in human subjects, which resulted in reduced biological efficiency. Many of the activity-established phyto principles have been rigorously restricted in their development because of their low solubility, diffusion, and bioavailability ( Badawi et al, 2020 ). Identification and oral supplementation of bioactive compounds for mitochondrial stimulation, such as lipolytic potential with the functional stimulation of β-adrenergic receptor followed by the activation of AMPK and CREBp-1, became very challenging because its low intracellular uptake ends with low biological availability and loss of efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Akbarian et al (2016) have found that the biological availability of orally supplemented basil seeds is very tracing in human subjects, which resulted in reduced biological efficiency. Many of the activity-established phyto principles have been rigorously restricted in their development because of their low solubility, diffusion, and bioavailability ( Badawi et al, 2020 ). Identification and oral supplementation of bioactive compounds for mitochondrial stimulation, such as lipolytic potential with the functional stimulation of β-adrenergic receptor followed by the activation of AMPK and CREBp-1, became very challenging because its low intracellular uptake ends with low biological availability and loss of efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compound across the cellular lipid bilayer without covalent modification or conformational change may provide maximum efficiency and deserve their application in obesity treatment. In the modern approach, the applications of SLNp as a carrier in facilitating the effective diffusion through the cell membrane increased the bioavailability of active ingredients such as silymarin, berberine, triptolide, metformin, and pomegranate extract for antiobesity and anti-inflammatory treatment, which is most successful ( Xue et al, 2015 ; Mohseni et al, 2019 ; Badawi et al, 2020 ). We have selected chia seed phospholipid as the encapsulating material because of its recommended ratio of omega 3 and omega 6 with lipolytic potential ( Pandurangan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of nanoparticles is commonly indicated by ZP which is employed to measure the nanoparticles’ charge (Badawi et al., 2020 ). ZP of the developed formulations ranged from −25.0 to −32.1 mV ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…ZP of the developed formulations ranged from −25.0 to −32.1 mV ( Table 2 ). The prepared formulations exhibited negative zeta potential due to the occurrence of terminal carboxylic groups in the lipids (Badawi et al., 2020 ). It is worth stating that there was a small difference in ZP values, but the variation was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of essential oils has also been encapsulated in SLNs [ 147 ]. In particular, SLNs loaded with Z. multiflora essential oil have been prepared [ 148 ].…”
Section: Organic-based Delivery Systemsmentioning
confidence: 99%